The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/tie.21925
|View full text |Cite
|
Sign up to set email alerts
|

Green marketing cradle‐to‐cradle: Remanufactured products in Asian markets

Abstract: Remanufacturing, a key circular economy practice, is a new way of sustainable thinking without depleting additional economic resources. Because remanufactured goods come from direct reuse of returned or already used goods, the environmental impacts of production are reduced and product longevity is extended; therefore, these products can be considered “green products.” Are they appealing to the green consumers, however? Our questionnaire survey of more than 1,168 consumers from eight Asian countries shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 78 publications
(112 reference statements)
4
35
1
Order By: Relevance
“…Remanufactured products are relevant to CE as it has economic, social and environmental benefits (Wang & Hazen, 2016;Wang & Kuah, 2018). In this context, remanufacturing represents a key CE practice since remanufactured products are made through the reuse of materials directly in the production process, thus this strategy is more environmental friendly when compared to other sustainable production techniques such as recycling (Wahjudi et al, 2018;Wang & Kuah, 2018). However, these products need to be accepted by consumers for the successful adoption of CE (Singhal, Jena, & Tripathy, 2019).…”
Section: Circular Economy and Remanufactured Productmentioning
confidence: 99%
See 1 more Smart Citation
“…Remanufactured products are relevant to CE as it has economic, social and environmental benefits (Wang & Hazen, 2016;Wang & Kuah, 2018). In this context, remanufacturing represents a key CE practice since remanufactured products are made through the reuse of materials directly in the production process, thus this strategy is more environmental friendly when compared to other sustainable production techniques such as recycling (Wahjudi et al, 2018;Wang & Kuah, 2018). However, these products need to be accepted by consumers for the successful adoption of CE (Singhal, Jena, & Tripathy, 2019).…”
Section: Circular Economy and Remanufactured Productmentioning
confidence: 99%
“…The remanufacturing process includes benefits for companies in economic, social and environmental aspects, besides assists in the successful implementation of the CE by organizations (Wang & Hazen, 2016). Therefore, remanufactured products are essential for the successful adoption of the CE, since the items produced reuse materials that would be directly discarded in the manufacturing process and reduce the negative impact on the environment of the company's production processes (Wang & Kuah, 2018). Thus, these products are considered sustainable since their manufacturing process minimizes negative impacts caused to the environment (Michaud & Llerena, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Green marketing runs the campaigns for creating awareness in the public related to the diseases and illness caused by the food. Several researches by different researchers (Wang & Kuah, ) have been conducted to observe the effect of the green marketing on the health consciousness. The health consciousness behavior is motivated in the individuals by the health awareness campaigns by the green marketing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a review of the literature since the 1990s, we found the many businesses [1][2][3][4][5][6][7][8][9][10][11][12] and researchers that benefited from green marketing continue to rely on these benefits nearly 30 years later [13][14][15][16]. We define green marketing as the set of activities designed to generate and facilitate any exchange aimed at satisfying human needs or desires, in such a way that these needs and desires are met, with a minimum harmful impact on the natural environment.…”
Section: Introductionmentioning
confidence: 99%